Green supply chain management practices and performance in Omani oil and gas companies: Employees’ perceptions - Al Isaii, Imad 'Abdullah Salim (2024)
Green Supply Chain Management (GSCM) plays a significant role in determining the success of oil and gas companies. Despite the relevance and applicability of GSCM practices to oil and gas companies, the previous research reveals that there is limited research attempted to investigate the effect of GSCM practices on the environmental impact and operating cost performance of oil and gas companies in Oman. The lack of GSCM practices has resulted in the oil and gas industry being a significant source of pollution. However, Oman is seen to be reluctant in implementing these practices due to the associated costs. The aim of the study is to investigate the relationship between GSCM practices and environmental and operating cost performance in Oman oil and gas companies. Five dimensions of GSCM are used in this study, which are Internal Environmental Management (IEM), Green Purchasing (GP), Cooperation with Customers (CC), Eco-Design, and Investment Recovery. Whilst, two dependent variables, which are environmental and operational cost performance are investigated to be related to these five GSCM dimensions. The primary data was collected from 320 respondents from 16 companies using a simple random sampling technique. This study employed specific testing procedures, including T-test, correlation, ANOVA, and multiple linear regression analysis to test the hypotheses. The data analysis was performed using the Statistical Package for Social Sciences (SPSS) program, version 22. The results of the analysis indicate that GSCM practices adopted by the oil and gas firms are significantly associated with their performance. The findings suggest that the overall competency of GSCM practices have a positive and significant impact on both environmental and operational cost performance. This study reveals the importance of GSCM practices despite the incurring cost during implementation period. Thus, future research can use different techniques in ensuring GSCM been practice among oil and gas companies.